Crab diversity as support for ecotourism activities in Pejarakan Mangrove Forest, Buleleng, Bali, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ginantra IK, Muksin IK, Joni M. 2021. Crab diversity as support for ecotourism activities in Pejarakan Mangrove Forest, Buleleng, Bali, Indonesia. Biodiversitas 22: 4139-4145. This research aims to determine the diversity of crabs to support ecotourism activities in the coastal mangrove forest of Pejarakan Buleleng. Sampling of crabs was carried out using the square method, as many as 23 squares were spread over three mangrove zones, namely the front zone, the middle zone, and the rear zone. The number of individual crustacean species in each square plot was counted. Crab identification is based on morphological characters (shell color, claw shape, body-color, body size). Habitat use activities are observed directly. The diversity of crabs was calculated using the Shannon-Wiener diversity index. The results showed that in the coastal mangrove area of Pejarakan Buleleng, there were 11 species of crabs (9 species of crabs and 2 species of hermit crabs). Species diversity is in the medium category (index 2.25) and evenness index is high (E = 0.93, mangrove conditions are stable). The seaward mangrove zone shows a higher diversity of crab species than the middle zone and the rear zone. The species of crabs that are quite abundant in the three zonings are Uca vocans, Chiromanthes sp., and Coenobita sp. Characteristics of crabs, activities, habitat use in mangrove zoning are attractions for ecotourism activities.
Keywords: species diversity, crustaceans, mangroves, ecotourism attractions